New coating formulation for the slow release of urea using a mixture of gypsum and dolomitic limestone - Babadi, Farahnaz Eghbali; Yunus, Robiah; Abdul Rashid, Suraya; Mohd Salleh, Mohamad Amran; Ali, Salmiaton (Elsevier, 2015)
The use of urea and urea-based fertilizers has increased considerably over the past 15 years. They currently account for approximately 51% of the world's agricultural nitrogen consumption. However, about 20–70% of the applied urea fertilizer is lost to the environment, causing serious pollution and increasing costs. These losses come from leaching, decomposition, and ammonium volatilization in the soil during handling and storage. Controlled release by coating can be used to increase urea fertilizer efficiency. We studied the use of gypsum, sulfur, and ground magnesium lime as cost-effective coating materials. All these coating materials contain nutrients required by plants. The effects of the coating composition and proportion of sealant on the rate of urea release and the crushing strength of the coated urea were investigated. We found that coated urea with the same proportion of gypsum–ground magnesium lime (GML) exhibited low urea release and high crushing strength. The performance was enhanced when using polyols as a sealant on the surface of the coated urea. A surface morphology analysis indicated a uniform and smooth surface on the coated film. The efficiency of the coated urea improved by 34.2% when using gypsum–GML (1:1 ratio) containing 1.1% polyols.